Novel nomogram for predicting survival in advanced non-small cell lung cancer receiving anti-PD-1 plus chemotherapy with or without antiangiogenic therapy - Wu, Yahua; Lv, Chengliu; Lin, Mingqian; Hong, Yaping; Du, Bin; Yao, Na; Zhu, Yingjiao; Ji, Xiaohui; Li, Jiancheng; Lai, Jinhuo (Frontiers in Immunology, 2023)
Background: This study aimed to develop and validate a novel nomogram to predict survival in advanced non-small cell lung cancer (NSCLC) receiving programmed cell death 1 (PD-1) inhibitor plus chemotherapy with or without antiangiogenic therapy.Methods: A total of 271 patients with advanced NSCLC who received anti-PD-1 plus chemotherapy with or without antiangiogenic therapy were enrolled in our center and randomized into training cohort (n=133) and internal validation cohort (n=138). Forty-five patients from another center were included as an independent external validation cohort. The nomogram was created based on the multivariate cox regression analysis to predict overall survival (OS) and progression-free survival (PFS). The performance of the nomogram was assessed using the concordance index (C-index), the time-dependent area under the receiver operating (ROC) curves (AUCs), calibration curves, and decision curve analysis (DCA).Results: Four factors significantly associated with OS were utilized to create a nomogram to predict OS: Eastern Cooperative Oncology Group performance status (ECOG PS), programmed cell deathligand 1 (PD-L1) expression, chemotherapy cycle and pre-treatment lactate dehydrogenase-albumin ratio (LAR). Six variables significantly associated with PFS were incorporated into the development of a nomogram for predicting PFS: ECOG PS, histology, PD-L1 expression, chemotherapy cycle, pre-treatment platelet to lymphocyte (PLR) and pre-treatment LAR. The C-indexes of the nomogram This is a provisional file, not the final typeset article for predicting OS and PFS were 0.750 and 0.747, respectively. The AUCs for predicting 0.791, 0.776 and 0.810, 0.787, 0,861, respectively. The calibration curves demonstrated a good agreement between predictions and actual observations. The DCA curves indicated that the nomograms had good net benefits. Furthermore, the nomogram model was well validated in the internal and external cohorts.The novel nomogram for predicting the prognosis of advanced NSCLC receiving anti-PD-1 plus chemotherapy with or without antiangiogenic therapy may help guide the clinical.